The Reform of FBI Intelligence Operations - Elliff, John T. (Book collections on Project MUSE., 1979)
Acts of terrorist violence and foreign espionage may pose a serious threat to the security of the United States; yet recent disclosures demonstrate the great risk in giving an agency such as the FBI unlimited authority for gathering intelligence about terrorists and spies. Taking into account the findings and recommendations of the post-Watergate inquiries into FBI operations, John Elliff analyzes the legal and policy questions posed by a ""security police"" in a nation committed to constitutional government and the rule of law. The author draws on his experience both as principal consultan.